Examining whether learning outcomes are enhanced when L2 learners' cognitive styles match listening instruction methods. (April 2021) - Yeldham, Michael; Gao, Yu-Jing
Abstract: This study explored whether learning outcomes were enhanced when learners' cognitive styles matched listening instruction methods. The study was grounded in Aptitude-Treatment-Interaction (ATI) theory, which maintains that learners have particular strengths and that learning is enhanced when instruction matches these strengths. In previous research by the first author, two groups of learners had been taught, respectively, through strategy instruction, and an interactive approach combining instruction of strategies and bottom-up skills. The former method involves the use of more top-down, global processing, and the latter method places comparatively more emphasis on bottom-up, detail-oriented processing. In this current study, data from that research was reanalyzed to examine the interaction of cognitive style and instructional approach over time. This was done for two cognitive style dimensions, global vs analytic and the closely related field-dependent vs field-independent. Learner outcomes were examined on a number of dependent variables drawn from areas central to listener development, those of listening abilities, listening skills and strategies, and affective characteristics. The study found sufficient evidence to support the matching of either cognitive style dimension with the instruction methods. Implications for L2 listening instruction are discussed, together with some practical advice for teachers.